Influence of Inflammatory and Oxidative Stress Pathways on Longitudinal Symptom Experiences in Children With Leukemia. Issue 5 (October 2019) - Hockenberry, Marilyn J.; Pan, Wei; Scheurer, Michael E.; Hooke, Mary C.; Taylor, Olga; Koerner, Kari; Montgomery, David; Whitman, Susan; Mitby, Pauline; Moore, Ida
Purpose: The purpose of this study was to explore the influence of oxidative stress (F2-isoprostanes) and inflammatory (interleukin [IL]-8) biomarkers on symptom trajectories during the first 18 months of childhood leukemia treatment. Method: A repeated-measures design was used to evaluate symptoms experienced by 218 children during treatment. A symptom cluster (fatigue, pain, and nausea) was explored over four time periods: initiation of post-induction therapy, 4 and 8 months into post-induction therapy, and the beginning of maintenance therapy (12 months postinduction). F2-isoprostanes and IL-8 were evaluated in cerebrospinal fluid (CSF) samples collected at baseline (diagnosis) and then at the four time periods. The longitudinal relationships of these biomarkers with the symptom cluster were examined using the longitudinal parallel process. Results: Pain and fatigue levels were highest during the post-induction phases of treatment and decreased slightly during maintenance therapy, while nausea scores were relatively stable. Even in the later phases of treatment, children continued to experience symptoms. CSF levels of the biomarkers increased during the post-induction phases of treatment. Early increases in the biomarkers were associated with more severe symptoms during the same period; patients who had increased biomarkers over time also experienced more severe symptoms over time. Conclusions: Findings reveal that children experienced symptoms throughout the course of leukemia treatment and support hypothesized longitudinal relationships of oxidative stress and inflammatory biomarkers with symptom severity. Activation of the biomarker pathways during treatment may explain underlying mechanisms of symptom experiences and identify which children are at risk for severe symptoms.